2021
DOI: 10.1002/fsn3.2098
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5‐HT‐BDNF signaling axis in mediating synergistic antidepressant‐like effects after combined administration of two oligosaccharide esters

Abstract: Potential mechanisms of depression involving herbal medicines and their specific compounds include elevated 5‐HT level and downstream BDNF pathway. To identify potentially new combined therapeutic strategies, 3,6'‐disinapoylsucrose (DISS) and tenuifoliside A (TFSA) have been observed to show antidepressant‐like effects and its related 5‐HT‐BDNF pathway. We have tried to investigate whether combined administration of DISS and TFSA exerted more effective in the treatment of depression, as assessed through tail s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…5-HT stimulates BDNF expression while BDNF promotes the neurogenesis and neuronal survival of 5-HT. Impairment in the 5-HT-BDNF signaling mechanism has been implicated in the pathophysiology of depression [120,121]. The administration of Lactobacillus helveticus and citalopram, an antidepressant of the SSRI class, in rodent models demonstrated similar outcomes of increased levels of 5-HT with anti-depressive effects.…”
Section: Inflammationmentioning
confidence: 99%
“…5-HT stimulates BDNF expression while BDNF promotes the neurogenesis and neuronal survival of 5-HT. Impairment in the 5-HT-BDNF signaling mechanism has been implicated in the pathophysiology of depression [120,121]. The administration of Lactobacillus helveticus and citalopram, an antidepressant of the SSRI class, in rodent models demonstrated similar outcomes of increased levels of 5-HT with anti-depressive effects.…”
Section: Inflammationmentioning
confidence: 99%
“…Brain‐derived neurotrophic factor (BDNF) is a member of the family of neurotrophic growth factors. It has been demonstrated that serum or plasma BDNF levels are decreased in depressed patients, as compared to the healthy controls, and attenuated BDNF levels are boosted by antidepressants (Gonul et al, 2005 ; Jones & Reichardt, 1990 ; Yang et al, 2021 ). On the other hand, previous research suggests that hesperidin exhibits antidepressant‐like properties due to induced BDNF in the hippocampus (Donato et al, 2014 ; El‐Marasy et al, 2014 ; Kosari‐Nasab et al, 2018 ; Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%